2007
DOI: 10.1071/rdv19n1ab110
|View full text |Cite
|
Sign up to set email alerts
|

110 Comparison of Andromed®, Bioxcell®, and Botu-Bov® Extenders for Cryopreservation of Bull Sexed Semen

Abstract: Sexing semen has become a worldwide technology now available in many countries through the use of flow cytometry for sexing mammal sperms (Johnson and Welch 1999 Theriogenology 52, 1323–1341). Because straws containing sexed semen have a low concentration, any condition that either improves or decreases freezing capabilities will considerably change semen quality. During cryopreservation, spermatozoa have been described as undergoing many changes that lead to membrane damage, which may result in decreased fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…The present study showed that Bioxcell extender was better than AndroMed and egg yolk extenders in terms of low incidence of sperm CI in one bull and low percentage of hyperactivated sperm motility in all bulls. These results were consistent with findings of previous reports on frozen bull semen (Braga et al. 2006; Celeghini et al.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present study showed that Bioxcell extender was better than AndroMed and egg yolk extenders in terms of low incidence of sperm CI in one bull and low percentage of hyperactivated sperm motility in all bulls. These results were consistent with findings of previous reports on frozen bull semen (Braga et al. 2006; Celeghini et al.…”
Section: Discussionsupporting
confidence: 94%
“…The present study showed that Bioxcell extender was better than AndroMed and egg yolk extenders in terms of low incidence of sperm CI in one bull and low percentage of hyperactivated sperm motility in all bulls. These results were consistent with findings of previous reports on frozen bull semen (Braga et al 2006;Celeghini et al 2008). The presence of high antioxidant activity in Bioxcell might alleviate LPO-mediated sperm CI, hyperactivation and premature capacitation (Chatterjee and Gagnon 2001;Kasimanickam et al 2007;Stradaioli et al 2007).…”
Section: Discussionsupporting
confidence: 93%
“…It is well established that cryopreservation decreases spermatozoa viability, functionality, and fertilizing ability [19,39,48]. Furthermore, many factors affecting the success of REPS's cryopreservation have not been extensively studied, as in AV-and EE-collected ram spermatozoa [26,49].…”
Section: Discussionmentioning
confidence: 99%
“…They include those that are soy lecithin-based (AndroMed ® , BioXcell ® , Biociphos Plus ® , Botu-Bov ® -soy lecithin, and OviXcell ® ), egg-yolk-based (Biladyl ® , Botu-Bov ® Triladyl ® , and BullXcell ® ), milk-based (INRA96 ® ), and protein-free (OptiXcell ® ) [14][15][16][17][18]. Different studies were conducted on the effects of commercially prepared semen extenders on the freezability of the spermatozoa of bulls [15,16,19,20], buffalo [21], goat bucks [22], and rams [23][24][25]. In recent years, there has been a call by researchers against the use of egg-yolk-based extenders due to the wide variability of their components and microbial contamination risk, leading to endotoxin production, reducing spermatozoa post-thaw viability and acrosomal integrity [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Nehring and Rothe (2003) rate the phytoextender AndroMed ® lower than Triladyl ® , especially with low sperm numbers. Likewise, Braga et al (2006) found AndroMed ® to be less suitable. On the other hand, Mueller-Schloesser et al (1995) and Cho et al (2013) found no difference between Triladyl ® and Andromed ® .…”
Section: Discussionmentioning
confidence: 99%